Multifunctional Triamcinolone Acetonide Microneedle Patches for Atopic Dermatitis Treatment - Liwan Song; Lu Fan; Qingfei Zhang; Shanshan Huang; Bin Kong; Jian Xiao; Ye Xu (Small Structures)
Atopic dermatitis (AD), a chronic and inflammatory skin disease, has brought huge physiological and psychological burdens to patients, which causes wide concerns in society. Herein, a multifunctional microneedle (MN) patch is proposed integrated with a desirable moisturizer and intelligent drug delivery capacity for AD treatment. Such MN patch consists of hyaluronic acid (HA) backing and near‐infrared (NIR) responsive tips containing black phosphorous quantum dots (BPQDs), low‐melting agarose, polyvinylpyrrolidone (PVP), and triamcinolone acetonide (TA). Among them, the soluble HA serves as a long‐term moisturizer for relieving dryness symptoms of AD. By introducing the NIR excitable and photothermal responsive BPQDs into agarose, the state of the composite material can be adjusted intelligently via NIR, thus achieving controllable release of the encapsulated TA in tips. Besides, PVP with enough mechanical strength can help MNs successfully penetrate the thickened skin of AD patients. Based on these advantages, it is demonstrated that the multifunctional MN patch reveals a satisfactory therapeutic effect in the AD model of Balb/c mice. These results indicate the potential values of the proposed MN patch in the treatment of AD skin diseases and other related biomedical fields.